2008
DOI: 10.1097/ta.0b013e31818c10fc
|View full text |Cite
|
Sign up to set email alerts
|

Imaging May Delay Transfer of Rural Trauma Victims: A Survey of Referring Physicians

Abstract: Factors other than patient care dictate imaging acquisition in almost half of those surveyed. Misperception of expectations, misunderstanding of legal imperatives, and liability concerns all delay transport of the injured. ATLS-certified individuals use imaging more appropriately, thus, promoting more timely transfer. State-wide protocols, education, and liability reform may reduce transport delays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 22 publications
(22 reference statements)
0
29
0
Order By: Relevance
“…These guidelines are continually revised to adopt changes in technologies and techniques to improve patient outcomes (30,31). In the pediatric population, if the trauma is deemed severe enough to warrant transfer to a pediatric trauma center (PTC), ATLS guidelines recommend to promptly transfer the patient without any delay, even without imaging.…”
Section: Discussionmentioning
confidence: 99%
“…These guidelines are continually revised to adopt changes in technologies and techniques to improve patient outcomes (30,31). In the pediatric population, if the trauma is deemed severe enough to warrant transfer to a pediatric trauma center (PTC), ATLS guidelines recommend to promptly transfer the patient without any delay, even without imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of these nonclinical reasons included a misunderstanding of legal requirements, perceived expectations of the receiving trauma center, and concern about medical liability. 27 It is also possible that some of the CT imaging was obtained while waiting for a transport team or helicopter and therefore not the source of the delay but rather a consequence of a delay in the system.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, approximately 20% of all referred patients have at least one CT scan repeated upon admission [13]. The impact of delaying transfer for imaging purposes (performing or obtaining images) can result in delay in treatment without any realized patient benefits [14-16]. Lee et al conducted a survey of referring physicians and found that approximately 30% of the referring physicians believed that trauma centers require pre-referral images [16].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of delaying transfer for imaging purposes (performing or obtaining images) can result in delay in treatment without any realized patient benefits [14-16]. Lee et al conducted a survey of referring physicians and found that approximately 30% of the referring physicians believed that trauma centers require pre-referral images [16]. Concerns regarding liability issues and financial interests of referring centers are among other factors that contribute to pre-referral imaging.…”
Section: Introductionmentioning
confidence: 99%